How to do everything with Windows Mobile - McPherson, Frank (McGraw-Hill, 2006)
Get the most out of your Pocket PC, Pocket PC Phone, or Smartphone using the latest Windows Mobile software and this easy-to-follow guide. Learn fast and simple ways to manage all types of information-from everyday essentials such as scheduling appointments and storing addresses to balancing your checkbook and reading email-no matter where you go. Written in a step-by-step format, How to Do Everything with Windows Mobile shows you how to share data with other wireless devices, play music, watch videos, send messages, write letters, and much more. Whether your needs are business or pleasure, this handy guide will have you fully utilizing all of the expanded features and capabilities of your Windows Mobile device.